Lactic acid removal and heart rate frequencies during recovery after strenuous rowing exercise. Issue 4 (December 1985) - Koutedakis, Y; Sharp, N C
Abstract : Three tests were conducted to assess the effectiveness of three different intensities of exercise both in reducing blood lactic acid (LA) levels and in influencing subjects' heart rate (HR), following a 2000 m race in a rowing boat. In the first and second tests these variables were investigated during a 13 min recovery exercise at 60% and 40% of the preceding maximum rowing speed respectively. In the third test the subjects had a resting recovery. The results include a significant increase (P less than 0.001) in the rate of lactate removal following the 40% recovery compared with the 60% and resting recoveries. The HRs were significantly lower during the last minute of resting recovery compared with 40% and 60% recoveries (P less than 0.001). The same was true when 40% recovery was compared with 60% recovery (P less than 0.001). The present data suggest firstly that 40% of the maximum rowing speed is an appropriate pace for effective LA removal and secondly that, at least for trained rowers, 86% of their maximum HR can be taken as an indication of work of an intensity at or above anaerobic threshold.